2015
DOI: 10.3390/catal5042039
|View full text |Cite
|
Sign up to set email alerts
|

Selective Oxidation of Glycerol with 3% H2O2 Catalyzed by LDH-Hosted Cr(III) Complex

Abstract: A series of layered double hydroxides (LDHs) -hosted sulphonato-salen Cr(III) complexes were prepared and characterized by various physico-chemical measurements, such as Fourier transform infrared spectroscopy (FTIR), ultraviolet-visible spectroscopy (UV-Vis), powder X-ray diffraction (XRD), transmission electron microscope (TEM), scanning electron microscope (SEM) and elemental analysis. Additionally, their catalytic performances were investigated in the selective oxidation of glycerol (GLY) using 3% H2O2 as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…Some efforts have been dedicated to finding active materials for glycerol oxidation based on CuNi-Al layered double hydroxides and Mg–Al layered double hydroxides (LDHs) in combination with various transition metals (Cr, Mn, Fe, Co, Cu). Zhou et al incorporated various metals (Ni, Zn, Cu, Co, etc.) into Mg–Al LDHs and investigated the effect of the material composition on the catalytic performance for glycerol oxidation .…”
Section: Glycerol Oxidation Over Nonprecious Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some efforts have been dedicated to finding active materials for glycerol oxidation based on CuNi-Al layered double hydroxides and Mg–Al layered double hydroxides (LDHs) in combination with various transition metals (Cr, Mn, Fe, Co, Cu). Zhou et al incorporated various metals (Ni, Zn, Cu, Co, etc.) into Mg–Al LDHs and investigated the effect of the material composition on the catalytic performance for glycerol oxidation .…”
Section: Glycerol Oxidation Over Nonprecious Metalsmentioning
confidence: 99%
“…Wang et al reported in a series of studies the employment of sulphonato-salen-Cr 3+ complexes intercalated into Mg–Al LDHs (CrAlMg) as catalysts for the selective oxidation of glycerol under neutral or basic conditions. In the first study in 2012, the authors demonstrated that a selectivity toward dihydroxyacetone of 44% at a glycerol conversion of 73% was achieved over CrAlMg catalysts with 3% H 2 O 2 as oxidant under base-free conditions (60 °C, 4 h reaction time, atmospheric pressure) . It is noteworthy to mention that the best performance of the catalyst was observed to be at neutral pH with a decrease in conversion and selectivity toward dihydroxyacetone with lower or higher pH value.…”
Section: Glycerol Oxidation Over Nonprecious Metalsmentioning
confidence: 99%
“…The plot of the selectivity over the reaction time (Fig. 5) shows that the selectivity towards the C 3 products glyceric acid and tartronic acid increases within the first 1 to 1.5 h. At longer reaction times, increasing C-C cleavage into the C 2 and C 1 products oxalic acid, glycolic acid, and formic acid sets in, as it is also observed in the use of other non-noble 42,49 and noble 73 metal catalysts.…”
Section: View Article Onlinementioning
confidence: 66%
“…[37][38][39][40][41] However, there are only few reports on selective oxidation of glycerol in basic media with non-noble metal catalysts, such as with the toxic and carcinogenic cobalt, [42][43][44] layered double hydroxide supported transition metals, [45][46][47] or using hydrogen peroxide instead of molecular oxygen as an oxidizing agent. 48,49 Key factors for the fabrication of efficient supported catalysts are firstly a high dispersion of the active component on the support material; secondly, high surface areas of the support; and thirdly, large porosity to allow efficient diffusion of reactants to the active centers. A particularly intriguing support for Cu based catalysts is γ-Al 2 O 3 , in which Cu cations are atomically dispersed by occupying the tetrahedral and octahedral sites of Al 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…An interesting area of research for selective oxidation has seen a focus on lower temperature approaches in the liquid phase, as opposed to gas phase approaches at higher temperature [6]. In particular, the use of supported metal nanoparticles demonstrates great promise.…”
mentioning
confidence: 99%